Glycerophosphoinositol Promotes Apoptosis of Chronic Lymphocytic Leukemia Cells by Enhancing Bax Expression and Activation - Boncompagni, Gioia; Varone, Alessia; Tatangelo, Vanessa; Capitani, Nagaja; Frezzato, Federica; Visentin, Andrea; Trentin, Livio; Corda, Daniela; Baldari, Cosima T.; Patrussi, Laura (Frontiers in Oncology, 2022)
An imbalance in the expression of pro- and anti-apoptotic members of the Bcl-2 family of apoptosis-regulating proteins is one of the main biological features of CLL, highlighting these proteins as therapeutic targets for treatment of this malignancy. Indeed, the Bcl-2 inhibitor Venetoclax is currently used for both first-line treatment and treatment of relapsed or refractory CLL. An alternative avenue is the transcriptional modulation of Bcl-2 family members to tilt their balance towards apoptosis. Glycerophosphoinositol (GroPIns) is a biomolecule generated from membrane phosphoinositides by the enzymes phospholipase A(2) and lysolipase that pleiotropically affects key cellular functions. Mass-spectrometry analysis of GroPIns interactors recently highlighted the ability of GroPIns to bind to the non-receptor tyrosine phosphatase SHP-1, a known promoter of Bax expression, suggesting that GroPIns might correct the Bax expression defect in CLL cells, thereby promoting their apoptotic demise. To test this hypothesis, we cultured CLL cells in the presence of GroPIns, alone or in combination with drugs commonly used for treatment of CLL. We found that GroPIns alone increases Bax expression and apoptosis in CLL cells and enhances the proapoptotic activity of drugs used for CLL treatment in a SHP-1 dependent manner. Interestingly, among GroPIns interactors we found Bax itself. Short-term treatments of CLL cells with GroPIns induce Bax activation and translocation to the mitochondria. Moreover, GroPIns enhances the pro-apoptotic activity of Venetoclax and Fludarabine in CLL cells. These data provide evidence that GroPIns exploits two different pathways converging on Bax to promote apoptosis of leukemic cells and pave the way to new studies aimed at testing GroPIns in combination therapies for the treatment of CLL.